2020
DOI: 10.1093/jee/toaa232
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Two Commercial Insecticides on Egg Parasitoids (Hymenoptera: Scelionidae) of Green Stink Bugs (Hem: Pentatomidae)

Abstract: Pistacia vera L. is one of the most important horticultural crops in Iran. The stink bugs Acrosternum arabicum and Brachynema germari are two of the key pests that cause significant direct and indirect damage on Pistacia vera. Egg parasitoids have been considered as potential biological control agents of pistachio green stink bugs. Among them, Trissolcus semistriatus and Psix saccharicola are the most abundant and efficient parasitoid for A. arabicum in pistachio orchards. In this study, we assessed lethal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…However, contrary to our results, some studies reported that pyrethroids disrupt locomotor function and parasitoids' physical perception [20,71,72]. For instance, pyrethroids insecticides at sub-lethal doses could disturb some behavior parameters, decreasing the attack rates of Trissolcus semistriatus (Hymenoptera, Platygastridae) [73], the walking speed in Trissolcus basalis (Hymenoptera, Platygastridae) [20], and the oviposition behavior of A. ervi parasitizing M. persicae on oilseed rape [52]. An explanation of our results could be that parasitoid wasp rearing began from the mummies of M. persicae collected on peach orchards.…”
Section: Non-detrimental Effects Of Low Insecticide Concentrationscontrasting
confidence: 99%
“…However, contrary to our results, some studies reported that pyrethroids disrupt locomotor function and parasitoids' physical perception [20,71,72]. For instance, pyrethroids insecticides at sub-lethal doses could disturb some behavior parameters, decreasing the attack rates of Trissolcus semistriatus (Hymenoptera, Platygastridae) [73], the walking speed in Trissolcus basalis (Hymenoptera, Platygastridae) [20], and the oviposition behavior of A. ervi parasitizing M. persicae on oilseed rape [52]. An explanation of our results could be that parasitoid wasp rearing began from the mummies of M. persicae collected on peach orchards.…”
Section: Non-detrimental Effects Of Low Insecticide Concentrationscontrasting
confidence: 99%
“…Our toxicity assay results showed that bifenazate is a potential insecticide for effective control of P. citri ; However, insecticide has not only acute toxicity, but also the sublethal effects 38 . In the current study, the fecundity of P. citri was decreased in the LC 10 or LC 30 treated groups, and the same response was observed in pests treated with other insecticides 39 .…”
Section: Discussionmentioning
confidence: 82%
“…brassicae were fed to eggs of Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) treated with Bacillus thuringiensis Berliner (Bacillales: Bacillaceae) 78 and eggs of Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae) treated with LC 30 of diazinon 76 . Apart from Trichogramma , a shift in the functional response was also observed for other parasitoids and predators under the exposure of different concentrations of different insecticides 82–84 . The difference in the type and parameters of functional response is due to various factors, namely exposure to pesticides, bio‐agents under study, multigenerational and transgenerational effects, differences in the host species, and laboratory conditions 46,63,84 …”
Section: Discussionmentioning
confidence: 97%
“…76 Apart from Trichogramma, a shift in the functional response was also observed for other parasitoids and predators under the exposure of different concentrations of different insecticides. [82][83][84] The difference in the type and parameters of functional response is due to various factors, namely exposure to pesticides, bio-agents under study, multigenerational and transgenerational effects, differences in the host species, and laboratory conditions. 46,63,84 Despite a change in the type of functional response upon exposure to different concentrations of insecticide, it resulted in increasing (except for the LC 50 ) the asymptote of the functional response curve as compared to the control.…”
Section: Discussionmentioning
confidence: 99%